PRODUK KAP LAMPU GANTUNG BERBAHAN LIMBAH TONGKOL JAGUNG SEBAGAI UPAYA MENGURANGI PENCEMARAN LINGKUNGAN - Fauzan Adimas (Ocean Engineering : Jurnal Ilmu Teknik dan Teknologi Maritim, 2022)
Based on the experimental study about corncob conducted before, this village has managed to create a new breakthrough production of processed foods such as corn chips since 2003. The foods that use raw materials of corn is the only one in Probolinggo. Corn chips production as small industries is run by 7 women farmers starting in 2008. (Wahmuda, 2013). The problem of this industrial activity is unbalancing the marketing area with market demand that obstruct continues to increase. This causes decrease on the productivity of the industry. In addition corncob waste left over from a small industrial activities corn chips squashed every day as much as 60 kg. This would be a major obstacle when marketing targets to reach market demand. As a result of waste corn cobs will be more numerous and uncontrolled, even less the corn cob waste is only used as cooking fuel. This research includes experiments on corn cobs process is divided into several stages, namely the process of forming, heating, curing, mixing and merging material, as well as coloring. From the research-based experiments, it turns out corn cobs to have a variety of characteristics. The uniqueness and characteristics process of corncobs, can give some variant forms such as cubes, cylinders, triangles, and a chopped form. Of these forms can be created several patterns of merger between a very interesting form to be used as a hanging lamp shade products. In the manufacture of a hanging lampshade required supporting materials such as iron chandelier hook pipe diameter of 16 mm and an iron plate with a thickness of 3 mm. Innovation alternative these products will continue at the stage of the development process of product design by using corn cobs as raw material products with the hope to utilize more leverage on how to process forms such a way into a useful product in terms of people's needs, aesthetic value and become friendly products environment.